Mahdi Santoso, Yanciluk: PENGARUH EKSTRAKSI AIR PANAS DAN N-HEKSANA TERHADAP KARAKTERISTIK BAHAN BAKU DAN SIFAT REKAT PAPAN PARTIKEL PELEPAH NIPAH (Agrienvi: Jurnal Ilmu Pertanian, 2019)
Nipa (Nypa fruticans Wurmb) is a non wood lignosellulosic materials that potential as raw material ofcomposite board. One of disadvantage of the nipa fronds was contains are very high extractives and inorganicsubstances. The presence of high content of extractives in raw material of particle board potentially be an obstacle inthe process of gluing the composite board. The existing of extractive substances on the surface of the compositeboard raw materials contribute to make the bonding process is not going well. On the other side, the utilization ofnatural binder for non wood composite is still limited. This research focused to investigated the effects of extractivesubtances for bonding performance of natural binder such as citric acid for nipa fronds particleboard. The particlesscreened passed through aperture sizes of 10 mesh and treated with three condition (non extraction, hot waterextraction and n-hexana extraction) were used as materials in this research. Addition of natural binder of 10% basedon air dried particles was done and pressing temperature was set at 180ÂºC under a pressure of 3,6 MPa during 10minutes. The physics and mechanics properties of particleboard was tested by standard JIS A 5908:2003. Theresults showed that the extractiction treatments for raw material affects on the properties of the particleboards. Hotwater extraction treatment was able to give the best results. The properties of particleboard was density 0.84 g.cm-3;moisture content 7.44%; thickness swelling 1,12%; water absorption 21,83%; surface roughness 7.57 ?m; internalbonding 0.49 MPa; modulus of rupture 10.42 MPa and modulus of elasticity 3.65 GPa. All of the properties of nipafronds particleboard meet most of the standards JIS A 5908:2003.Keywords: Hot water extraction, n-hexane extraction, nipa frond particleboard, natural binder, citric acid.